Macrophages Break Interneuromast Cell Quiescence by Intervening in the Inhibition of Schwann Cells in the Zebrafish Lateral Line - Lin, Meng-Ju; Lee, Chia-Ming; Hsu, Wei-Lin; Chen, Bi-Chang; Lee, Shyh-Jye (Frontiers in Cell and Developmental Biology, 2022)
In the zebrafish lateral line system, interneuromast cells (INCs) between neuromasts are kept quiescent by underlying Schwann cells (SWCs) and lateral line nerve. Upon severe injuries that cause the complete loss of an entire neuromast, INCs can occasionally differentiate into neuromasts but how they escape from the inhibition by SWCs is still unclear. Using a genetic/chemical method to ablate a neuromast precisely, we found a small portion of larvae can regenerate a new neuromast, but the regeneration was hindered by inhibiting macrophages. By using in toto imaging, we further discovered heterogeneities in macrophage behavior and distribution along the lateral line. We witnessed the crawling of macrophages between the injured lateral line and SWCs during regeneration and between the second primordium and the first mature lateral line during development. It implies that macrophages may physically alleviate the nerve-derived inhibition to break the dormancy of INCs during regeneration by elevating Wnt activity in the zebrafish lateral line.